The classics magpie : a cornucopia of classical curiosities, fascinating facts and astonishing anecdotes from the ancient world /: a cornucopia of classical curiosities, fascinating facts and astonishing anecdotes from the ancient world. (2014) - Hood, Jane C
No abstract available